The Principal’s Effective Leadership in Elementary Education - Mukhtar Hadi (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2019)
The importance of effective management in educational organizations is getting more and more attention from various parties. The purpose of this study was to find out whether the heads of Madrasah Ibtidai'yah in Metro City had implemented effective leadership patterns in leadership management in madrasah. The results of this study indicate that the heads of Islamic elementary schools in Metro City are actually principals who present themselves as effective leaders and understand well how to become professional leaders. The professional meaning here is that the head of the madrasah has shown itself to be an education leader and always maintains quality at all times. In certain circumstances the head of the madrasah has even included the category of master school leaders who are able to show quality where other parties can place the principal as an expert in leading the school. The principal not only looks good, but also is able to show understanding of the meaning of quality. However, there has not been seen any influence between the headmaster's leadership and the level of achievement achieved by students. This means that principals actually include educational leaders with the title of professionals or even masters, but there is no significant influence between the level of leadership and student achievement.